2021
DOI: 10.1093/jmcb/mjab044
|View full text |Cite
|
Sign up to set email alerts
|

Emerging neurotropic features of SARS-CoV-2

Abstract: The prevailing coronavirus disease (COVID-19) caused by a novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) has presented some neurological manifestations including hyposmia, hypogeusia, headache, stroke, encephalitis, Guillain‒Barre syndrome, and some neuropsychiatric disorders. Although several cell types in the brain express angiotensin converting enzyme-2 (ACE2), the main SARS-CoV-2 receptor, and other related proteins, it remains unclear whether the observed neurological manifestations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 78 publications
0
9
0
3
Order By: Relevance
“…Neurological post-acute sequelae of SARS-CoV-2 infection (PASC) are common, although direct viral infection of the central nervous system (CNS) is rare [ 3 , 6 ]. Instead, inflammatory mechanisms, parenchymal hypoxia or microvascular injuries may contribute to the development of CNS injury, raising the possibility that these long-term symptoms may be accompanied by systemic biomarkers of neuronal damage or neuroinflammation.…”
mentioning
confidence: 99%
“…Neurological post-acute sequelae of SARS-CoV-2 infection (PASC) are common, although direct viral infection of the central nervous system (CNS) is rare [ 3 , 6 ]. Instead, inflammatory mechanisms, parenchymal hypoxia or microvascular injuries may contribute to the development of CNS injury, raising the possibility that these long-term symptoms may be accompanied by systemic biomarkers of neuronal damage or neuroinflammation.…”
mentioning
confidence: 99%
“…Despite the numerous reports on COVID-19, it is still debatable if SARS-CoV-2 invades the Central Nervous System (CNS) via olfactory neurons ( Brann et al, 2020 ) and infects neurons and glia of the CNS ( Zhan et al, 2021 ; Jacob et al, 2020 ; Song et al, 2021 ; Dobrindt et al, 2021 ; Pellegrini et al, 2020 ; Pedrosa et al, 2021 ; Wu et al, 2020b ; Yang et al, 2020 ). Different groups have shown that human neural progenitor cells, grown either as brain organoids or as neurospheres, are permissive to SARS-CoV-2 infection ( Song et al, 2021 ; Yang et al, 2020 ; Bullen et al, 2020 ; Ramani et al, 2020 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous reports on COVID-19, it is still debatable if SARS-CoV-2 invades the Central Nervous System (CNS) via olfactory neurons (27) and infects neurons and glia of the CNS (28)(29)(30)(31)(32)(33)(34)(35). Different groups have shown that human neural progenitor cells, grown either as brain organoids or as neurospheres, are permissive to SARS-CoV-2 infection (30,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%